Persistent hyperplastic primary vitreous – developmental anomaly of the eye in children - Kanigowska, Krystyna; Grałek, Mirosława; Klimczak-Ślączka, Dorota; Seroczyńska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Persistent hyperplastic primary vitreus in children continues to be a diagnostic and therapeutic challenge for ophthalmologists. It can occur in isolation, in association with other ocular disorders and rarely as a part of systemic disorder. Characteristic features include microphthalmic eye, white vascularized retrolental tissue with or without a persistent hyaloid artery, centrally dragged ciliary processes, an anteriorly shifted and (or) swollen lens, and varing degrees of lenticular opacification. PHPF is the most common associaton with unilateral cataracts. Differential diagnosis and functional effect of treatment are discussed.